Identification of miR-200a-5p targeting the peptide transporter TAP1 and its association with the clinical outcome of melanoma patients. (1st January 2020) - Lazaridou, Maria-Filothei; Gonschorek, Evamaria; Massa, Chiara; Friedrich, Michael; Handke, Diana; Mueller, Anja; Jasinski-Bergner, Simon; Dummer, Reinhard; Koelblinger, Peter; Seliger, Barbara
ABSTRACT: Tumor escape is often associated with abnormalities in the surface expression of the human leukocyte antigen class I (HLA-I) antigens thereby limiting CD8 + cytotoxic T cell responses. This impaired HLA-I surface expression can be mediated by deficient expression of components of the antigen processing and presentation machinery (APM) due to epigenetic, transcriptional and/or post-transcriptional processes. Since a discordant mRNA and protein expression pattern of APM components including the peptide transporter associated with antigen processing 1 (TAP1) has been frequently described in tumors of distinct origin, a post-transcriptional control of APM components caused by microRNAs (miR) was suggested. Using an in silico approach, miR-200a-5p has been identified as a candidate miR binding to the 3ʹ untranslated region (UTR) of TAP1. Luciferase reporter assays demonstrated a specific binding of miR-200a-5p to the TAP1 3ʹ-UTR. Furthermore, the miR-200a-5p expression is inversely correlated with the TAP1 protein expression in HEK293T cells and in a panel of melanoma cell lines as well as in primary melanoma lesions. High levels of miR-200a-5p expression were associated with a shorter overall survival of melanoma patients. Overexpression of miR-200a-5p reduced TAP1 levels, which was accompanied by a decreased HLA-I surface expression and an enhanced NK cell sensitivity of melanoma cells. These data show for the first time a miR-mediated control of the peptide transporter subunit TAP1 in melanoma thereby leading to a reduced HLA-I surface expression accompanied by an altered immune recognition and reduced patients' survival. Abbreviations: Ab: antibody; ACTB: β-actin; APM: antigen processing and presentation machinery; ATCC: American tissue culture collection; β2 -m: β2 -microglobulin; BSA: bovine serum albumin; CTL: cytotoxic T lymphocyte; FCS: fetal calf serum; FFL: firefly luciferase; FFPE: formalin-fixed paraffin-embedded; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; HC: heavy chain; HLA: human leukocyte antigen; HLA-I: HLA class I; HRP: horseradish peroxidase; IFN: interferon; im-miR: immune modulatory miRNA; LMP: low molecular weight protein; luc: luciferase; MFI: mean fluorescence intensity; MHC: major histocompatibility complex; miR: microRNA; NC: negative control; NK: natural killer; NSCLC: non-small cell lung carcinoma; OS: overall survival; PBMC: peripheral blood mononuclear cells; RBP: RNA-binding proteins; RL: Renilla; RLU: relative light units; TAP: transporter associated with antigen processing; tpn: tapasin; UTR: untranslated region.